Factors Affecting Guidance and Counselling Programme in Primary Schools in Nairobi Province, Kenya - Ireri, Niceta; Muola, James M (Global Journal of Educational Research, 2010)
The objective of this study was to establish the factors that affect guidance and counseling in primary schools. Guidance and counseling seems not to be adequately helping pupils with physical and psychological problems in Nairobi province of Kenya. Many primary schools are faced with indiscipline and poor performance yet there is a guidance and counseling programme running in these schools. The sample of study was 234 respondents selected from a population of 10,000 primary school teachers in Nairobi city through the stratified and simple random methods. A questionnaire was used to collect data. The results showed that majority of the respondents do not regard guidance and counseling as a critical issue in the development of the pupils. Too, it was found that teachers’ attitudes, training in counselling, availability of time and facilities have a negative impact on the guidance and counselling programme. The Government and the schools’ management do not provide the needed infrastructure for guidance and counseling. It was recommended that training of teachers in guidance and counseling be given priority by the schools and the government.
Keywords: Guidance; counselling; primary school and factors